A RARE CASE OF BILATERAL SYMMETRICAL TEMPORO-PARIETAL EXTRADURAL HEMATOMA IN ROAD TRAFFIC ACCIDENT (Journal of Forensic Medicine & Toxicology, 2022)
The autopsy findings of extradural hematoma (EDH) are an uncommon consequence of head injury and bilateral symmetrical extradural hematoma is extremely rare. In the case presented here, the author has encountered a case of road traffic accident in which the bilateral extradural hematoma observed symmetrically over the both parietal areas of the brain during autopsy in association with subarachnoid hemorrhages, which was sufficient to cause death. The cases of bilateral EDH diagnosed in clinical settings with the help of CT scanning has been reported but diagnosis during the autopsy has not been reported till date. Hence, the case is presented here to discuss the autopsy diagnosis and its medicolegal implications.
Keywords: Extradural hematoma; Head injury; Autopsy; Intracranial hemorrhage; Forensic Pathology